Transcriptomic Analysis Reveals Potential Gene Regulatory Networks Under Cold Stress of Loquat (Eriobotrya japonica Lindl.) - Zhang, Jiaying; An, Haishan; Zhang, Xueying; Xu, Fangjie; Zhou, Boqiang (Frontiers in Plant Science, 2022)
Loquat (Eriobotrya japonica Lindl.) is one of the most economically important evergreen fruit crops in China, while it often suffered the injury of cold stress in winter and earlier spring, and the annual yield loss of loquat fruits caused by cold or freezing stress were immeasurable. However, knowledge about the physiological response and molecular mechanism under cold stress are still limited. To investigate the potential regulation mechanism pre- and post- cold stress in loquat, the changes of physiological indicators and a comparative transcriptome analysis was performed against a cold-resistant cv. ‘Huoju’ and a cold-sensitive cv. ‘Ninghaibai’. The results of physiological indicators related to cold resistance indicated that rachis was most sensitive to cold stress and was considered as the representative organ to directly evaluate cold resistance of loquat based on subordinate function analysis. Here, we compared the transcriptome profiles of rachis pre- and under-cold stress in ‘Huoju’ and ‘Ninghaibai’. A total of 4,347 and 3,513 differentially expressed genes (DEGs) were detected in ‘Ninghaibai’ and ‘Huoju’, among which 223 and 166 were newly identified genes, respectively, and most of them were functionally enriched into plant hormone signal transduction (Huoju: 142; Ninghaibai: 200) and there were higher plant hormones content and related DEGs expression levels in ‘Huoju’ than that of ‘Ninghaibai’. Moreover, a total of 3,309 differentially expressed transcription factors (DETFs) were identified and some DEGs and DETFs were screened to subject to co-expression network analysis based on the gene expression profile data. Some candidate DEGs, including UDP-glycosyltransferase (UGT), glycosyltransferase (GT), sugar phosphate/phosphate translocator (SPT), sugar transport protein (STP), proline-rich receptor-like protein kinase (PERK) and peroxidise (POD), were significantly affected by cold stress and the expression level of these genes obtained from Real-Time Quantitative RT-PCR were consistent with the pattern of transcriptome profile, which suggested that these genes might play vital roles in cold resistance of loquat. Our results provide an invaluable resource for the identification of specific genes and TFs and help clarify gene transcription during the cold stress response of loquat.